2010
DOI: 10.1359/jbmr.090716
|View full text |Cite
|
Sign up to set email alerts
|

Effects of denosumab on bone mineral density and bone turnover in postmenopausal women transitioning from alendronate therapy

Abstract: Patients treated with bisphosphonates for osteoporosis may discontinue or require a switch to other therapies. Denosumab binds to RANKL and is a potent inhibitor of bone resorption that has been shown to increase bone mineral density (BMD) and decrease fracture risk in postmenopausal women with osteoporosis. This was a multicenter, international, randomized, double-blind, double-dummy study in 504 postmenopausal women ! 55 years of age with a BMD T-score of À2.0 or less and À4.0 or more who had been receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
294
3
20

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 400 publications
(334 citation statements)
references
References 36 publications
17
294
3
20
Order By: Relevance
“…Despite all these limitations of our study, we found a clear positive effect of denosumab treatment. these results are in accordance with the already published data on denosumab efficacy in increasing BMD in comparison to placebo and bisphosphonates (3,10,13,15). in regards to the adverse events, denosumab was well tolerated by all patients with no serious adverse events, which is in full correlation with its SmPc and previously reported data (6,17,19).…”
Section: Safetysupporting
confidence: 92%
“…Despite all these limitations of our study, we found a clear positive effect of denosumab treatment. these results are in accordance with the already published data on denosumab efficacy in increasing BMD in comparison to placebo and bisphosphonates (3,10,13,15). in regards to the adverse events, denosumab was well tolerated by all patients with no serious adverse events, which is in full correlation with its SmPc and previously reported data (6,17,19).…”
Section: Safetysupporting
confidence: 92%
“…(11)(12)(13)(14)(15)(16)(17) Effects of most osteoporosis medications differ, however, in patients who have already been pretreated with other potent osteoporosis medications. (18)(19)(20)(21)(22)(23) This is certainly true of TPTD and PTH. (24)(25)(26)(27)(28)(29)(30) BMD responses to initial TPTD/PTH followed by potent antiresorptive therapy are substantial in both spine and hip sites as a result of the effects of both components of the treatment sequence.…”
Section: Introductionmentioning
confidence: 96%
“…If this remodeling process is interrupted by anti-resorptive drugs, microfractures will grow, fuse, and cause stress fractures [6]. The risk of AFFs is reported to increase with the increased duration of Bisphosphonate treatment, from 1.8 cases per 10 5 users per year of exposure in the first 2 years, to 113 cases per 10 5 users per year at 8 years of Bisphosphonate use [7]. Our patient developed her fracture after 6 years of Bisphosphonate use.…”
Section: Discussionmentioning
confidence: 99%